THE ROLE OF MOTIVATIONAL DETERMINANTS IN STUDENTS' ACADEMIC ACQUISITION (International journal of artificial intelligence, 2025)
This article analyzes the motivational determinants that influence students' academic performance in the learning process. The study highlights the influence of internal and external types of motivation on the effectiveness of assimilation based on the theory of self-determination. The results show that autonomous motivation, internal interest in learning, and a sense of competence are the main factors that increase the level of assimilation of students.